In situ soil cementation with ureolytic bacteria by surface percolation - Cheng, Liang; Cord-Ruwisch, R. (2012)
The possibility of using microbiological processes to improve the mechanical properties of soil by undisturbed in situ application has gained attention over recent years. This paper describes a new variation of in situ soil reinforcement technology based on microbially induced carbonate precipitation (MICP), which involves both the hydrolysis of urea by soil bacteria enzyme and calcium carbonate precipitation in the presence of dissolved calcium ions. In contrast to other previously published approaches, the current work uses surface percolation for in situ placement of bacteria and cementation solution. Bacteria could be immobilised over the full length of a 1. m column by surface percolation. To accomplish this it was necessary to percolate alternate solutions containing either bacteria or fixation solution containing calcium ions. The biologically triggered cementation resulted in homogeneous cementation over the entire length of the 1-m sand column. The efficiency of calcite crystals to form strength was found to be related to the pore water content of the continuously drained column with less water content enabling more efficient strength formation. Scanning electron microscopy supported the idea that lower water contents lead to selective positioning of crystals at the bridging points between sand grains. These findings imply that the cost of MICP technology can be reduced by optimising the conditions for effective crystals precipitation. This is expected to make this technology more readily acceptable for large scale applications. © 2012 Elsevier B.V.